Antara Cerita & Tradisi: Pelestarian Warisan Sastra Lisan Masyarakat Antargenerasi Melayu Desa Pelepak Pute, Pulau Belitung - M. Afifulloh; Putra Pratama Saputra; I Nyoman Pasek Darmawan (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Preserving oral literature allows a deeper understanding of the relationship between communities and their natural environment. Through stories and traditions, Indigenous knowledge about land, ecosystems, and sustainable practices is passed down, offering a holistic perspective rooted in environmental harmony. Oral literature also connects past and present, fostering identity and continuity across generations. Unfortunately, oral literature is often marginalized and forgotten by younger generations, placing it at risk of extinction. Yet it holds important cultural, historical, and social values that shape community ideologies. Without proper attention, the loss of these ancient stories could erode the moral and cultural foundations of societies like those in Bangka Belitung. To address this, a community engagement program will be implemented in Pelepak Pute Village, Belitung Island, aimed at protecting local oral literature. Activities will be conducted in four stages: preparation (coordination and initial survey), socialization (public outreach through lectures and discussions), training and mentoring (on oral literature preservation), and evaluation (to assess outcomes and determine follow-up steps). Expected outcomes include publication in national journals or proceedings, local media coverage (e.g., Bangka Pos), and increased knowledge and skills among village residents. This initiative represents a crucial step in preserving the intangible cultural heritage of Bangka Belitung and ensuring its transmission to future generations.